Scheduling and Monitoring of Water Supply Project at Jabalpur Using Management Tool Primavera - Dubey, Arun; Bandewar, Deepak; Patel, Rakesh (International Journal of Scientific Research in Civil Engineering, 2023)
Implementation of construction project needs a proper planning and scheduling is of vital importance for the project to be executed and run smoothly. A best schedule has to be prepared in such a way that meets the primary objectives of the total project. Those primary objectives are to create a quality project, completed on time, within budget, and in a safe work environment.Hence in this study an ongoing construction project is taken and the execution of the project is compared with the schedule with the help of Primavera P6. An ongoing water supply project in is selected and the activities pertaining to the preconstruction, substructure and superstructure is considered for comparison. From the study, it is found, how the project is planned, the sequence of work and linking relationships between activities for the whole project.This research is based on secondary as well as primary data. This investigation highlighted scheduling of PAYLI MULTI VILLAGE RURAL WATER SUPPLY SCHEME, DISTT. JABALPUR, NARSINGHPUR AND SEONI" for ultimate capacity of bringing 71 mld treated water (23 hours of pumping) from the backwater of Bargi Dam on river Narmada to 638 villages of Jabalpur, Narsinghpur and Seoni districts in Single Package.
Keywords: Primavera; Gantt Chart; Time-Cost Comparison; Cpm Network; Tracking; Project Scheduling